Model Kepemimpinan Kepala Sekolah di Mts Pakis Gununglurah Cilingok BANYUMAS - Ahmad Nurbekti (DIMAR: Jurnal Pendidikan Islam, 2020)
Madrasah Tsanawiyah PAKIS is the first formal middle school that was established in a forest area to be precise in Pesawahan Hamlet, Gununglurah Village, Cilongok District, Banyumas Regency. In its implementation, the principal as a leader in educational institutions has a unique pattern or way of fostering student interest in learning. So the purpose of this study is to find out more about the Principal Leadership Model in Mts PAKIS Gunung Lurah Cilongok Banyumas. This research is a descriptive study using a qualitative approach. Data sources include the principal, teaching volunteers, students of MTs PAKIS, and community elements around MTs PAKIS. Data collection techniques through interviews, observation, and documentation study. The data validity was done by triangulating the sources and techniques. The data analysis technique used is the qualitative data analysis technique of the Milles and Huberman model. The results of this study explain that the principal leadership model in Mts PAKIS uses a participatory approach and has a tendency (Consideration). In its implementation, namely by bringing in Educator Volunteers who have various backgrounds, it has been proven to be able to foster student interest in learning.